Sustainable collaboration on complex problems: a “who” not a “what” challenge - Gibson, Josie (Frontiers in Research Metrics and Analytics, 2023)
Despite decades of collective efforts and many millions of dollars of investment, collaborations created to address wicked problems - complex issues that span industries and sectors - have had mixed success. The wicked problems terrain is tribal and contested by proponents of competing collective change and innovation tools and methodologies, advocates of different leadership approaches and, in recent years, big business champions who claim private enterprise is the most effective driver of ambitious solutions. This article argues that while all these elements deserve attention, the primary focus of many collaborations is heavily biased toward 'what' and 'how' questions - governance, processes, activities, metrics and outcomes - at the expense of the 'who' component: the leaders and networks of relationships required to sustain collective efforts. This is crucial given the gruelling realities of multi-year undertakings. Relational infrastructure may take the form of coalitions or taskforces called upon to create new approaches when previous efforts have failed. These groups are often led by people in formal and informal roles of leadership, authority and influence. This article explores the tension between the bias for governance, process and action and the need to develop robust leadership abilities and social ties. It draws on, among others, field experience and theories in leadership, adult development, complexity and systems thinking. It discusses leadership as a both an individual and a collective capability and highlights the need for better understanding of its significant role in anchoring, shaping and guiding effective system-based efforts that achieve positive impact.